Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1016/s0002-8703(96)90082-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose dobutamine echocardiography and rest-redistribution thallium-201 tomography in the assessment of spontaneous recovery of left ventricular function after recent myocardial infarction

Abstract: Spontaneous improvement of contraction and perfusion occurs after acute myocardial infarction. The relative merit of low-dose dobutamine stress echocardiography (LDDE) and rest-redistribution thallium scintigraphy (RR TI) in this setting has not been evaluated. We studied 30 patients at 7 +/- 3 days after acute myocardial infarction with LDDE (5 to 10 micrograms/kg/min) and RR TI single photon emission computed tomography. Viability was defined as improvement of wall thickening at LDDE in the presence of redis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…26) Moreover, it has been reported that LDSE (5 and 10µg/kg/min only) 5 to 14 days after acute myocardial infarction was as sensitive but more specific than rest-redistribution thallium-201 scan for reversible dysfunction by echocardiography 3 months later. 8,27) Dobutamine stress echocardiography is more accurate, especially in akinetic segments, and is minimally influenced by clinical factors. 8) The only clinical factor that reduced accuracy is a nonanterior infarction location.…”
Section: Discussionmentioning
confidence: 99%
“…26) Moreover, it has been reported that LDSE (5 and 10µg/kg/min only) 5 to 14 days after acute myocardial infarction was as sensitive but more specific than rest-redistribution thallium-201 scan for reversible dysfunction by echocardiography 3 months later. 8,27) Dobutamine stress echocardiography is more accurate, especially in akinetic segments, and is minimally influenced by clinical factors. 8) The only clinical factor that reduced accuracy is a nonanterior infarction location.…”
Section: Discussionmentioning
confidence: 99%
“…Precise, quantitative measurements of myocardial function (strain) may allow clinicians to detect ischemia during stress testing with lower doses of inotropic agents. Also, the detection of functional recovery in stunned myocardium during low dose dobutamine infusion may be used to detect viable myocardium (10)(11)(12)(13)(14); this requires a technique that is very sensitive to small changes in myocardial strain. In this paper, we present a method for reconstructing a three-dimensional strain field of the left ventricle (LV) from a collection of tagged MR images.…”
mentioning
confidence: 99%
“…The relative merit of these parameters was demonstrated to detect myocardial viability before successful revascularization, 13,22) but the optimal diagnostic approaches using these parameters simultaneously for identifying myocardial stunning after reperfusion and for predicting the final functional recovery have not been clarified in the clinical setting. In the present study, the usefulness of simultaneous evaluation of contractile reserve, perfusion, and free fatty acid metabolism at dobutamine stress testing for diagnosing myocardial stunning was clarified.…”
Section: Discussionmentioning
confidence: 99%